Evaluating Whether Indonesia Should Maintain or Revise Its Local Incorporation Requirement for Foreign Investors - Hawin, M; Butt, Simon; Setianingrum, Reni Budi (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2024)
The article reviews the locally incorporated company requirement for foreign investors in Indonesia. It uses a normative juridical method, focusing on examining positive law through a statute approach. It involves analyzing relevant laws, regulations, cases, and literature and includes interviews with law scholars and an official from Indonesia’s Investment Coordinating Board to gather expert opinions. The data obtained is analyzed using qualitative techniques. It discusses the advantages and disadvantages of the requirement in international foreign investment law and Indonesia concluding that its advantages outweigh the disadvantages, and some of the disadvantages have been resolved. Hence, the article argues that the requirement remains appropriate for Indonesia and should be maintained. However, certain investment treaties have weakened the requirement as a defense against legal action by locally incorporated companies in international arbitration. To overcome this problem, the country should renegotiate its bilateral investment treaties (BITs) that give the companies direct legal action rights and develop new BITs that contain balanced rights between foreign investors and Indonesia. Additionally, the locally incorporated company requirement should be reinforced by Indonesia’s negative list policy, prioritizing specific sectors for local investors.